Synthesis And Characterization Of Polyaniline/Multiwalled Carbon Nanotubes Based Nanocomposites - Razak, Saiful Izwan Abd (2010)
Polyaniline/multiwalled carbon nanotubes-manganese dioxide (PANI/MWCNTs-MnO2) nanocomposites were synthesized and characterized. MnO2 filling in the cavities of the MWCNTs were successfully done with clean outer surface as seen by transmission electron microscope (TEM). Ammonium persulphate ((NH4)2S2O8) oxidant proved to be desirable for the formation of PANI for the nanocomposite. The electrical conductivity of the polymerized PANI was at 38.34 Scm-1 with a fiber-like structure as observed by TEM. New para-hydroxybezene sulfonic acid (PHBSA) doped ex-situ nanocomposites exhibit improved electrical conductivity and interfacial interaction compared to the pristine ex-situ nanocomposite without PHBSA. TEM demonstrated clearly the improved bonding at the interface with electrical conductivity up to 39.26 Scm-1. New PANI/MWCNTs- MnO2 nanocomposites were developed by in-situ method. The MnO2 filling showed enhanced and desirable effect on the nanocomposite. Structural and thermal studies showed that the interaction between PANI and MWCNTs was more favorable with the addition of MnO2. The formation of PANI was more uniform and thin on the surface of MWCNTs-MnO2 with higher electrical conductivity compared to the unfilled nanocomposite. The PANI/MWCNTs-MnO2 nanocomposites at different loading showed that the electrical conductivity increasing amount of MWCNTs- MnO2.